NOTARY EMERITUS' LIABILITY FOR DEEDS MADE AFTER THE TERM OF OFFICE ENDS - Setiawan, Eileen Gani; Dharsana, I Made Pria (Ridwan Institute, 2024)
The notary emeritus is a member of the Notary Commission on Discipline, Protection of the Constitution, and the Ministry of Public Works and Public Works. This study aims to examine the legal principles and written legal sources. The study contributes to the understanding of the continuity of notarial duties and the potential legal ramifications for such activities. In this study, it will be systematically explained about the regulations that regulate certain legal categories, analyze the relationship between these regulations, and correlate them with existing problems. In addition, this study discusses the validity of deeds made by or before his term of office ends and the responsibility of the notary for the deedas he makes after his terms of office end.